2020
DOI: 10.1021/acs.macromol.0c00295
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effect on the Surface of a Metal–Organic Polyhedron: Tunable Thermoresponsiveness and Water Permeability

Abstract: Materials under space confinement can alter their physical and chemical properties, paving the way for new science and novel applications. Nanoparticles can enforce spatial constraints on the polymers densely grafted on their surfaces, which can effectively change polymers’ thermal/mechanical properties and finally lead to significant mechanical reinforcement for the obtained nanocomposites. Here, we describe the confinement effect that metal–organic polyhedron (MOPs), nanoparticles with monodispersed and ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…Ligand exchange dynamics among MOPs in their bulks. Originated from the hierarchically constrained dynamics of MOP ligands, [25][26] the ligand exchange on MOP surface demonstrates logarithmic kinetics, which is distinct from the ligand exchange kinetics of simple coordination complexes (usually first order reaction kinetics). [27][28] This finally enables the unique thermally activated polymer network dynamics rather than fast dynamics feature of that from simple coordination complex.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand exchange dynamics among MOPs in their bulks. Originated from the hierarchically constrained dynamics of MOP ligands, [25][26] the ligand exchange on MOP surface demonstrates logarithmic kinetics, which is distinct from the ligand exchange kinetics of simple coordination complexes (usually first order reaction kinetics). [27][28] This finally enables the unique thermally activated polymer network dynamics rather than fast dynamics feature of that from simple coordination complex.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, SAS has become a powerful tool in the study of porous NPs such as {Mo 132 } and metal-organic polyhedra (MOPs) (Fig. S1) (Yin et al, 2016;Zhang et al, 2019;Lai et al, 2020;Abourahma et al, 2001;Eddaoudi et al, 2001). Conventionally, the SAS data of these NPs are fitted by a coreshell model.…”
Section: Examples and Discussionmentioning
confidence: 99%
“…[ 65 ] The same approach was later used by Yin et al using poly( N ‐isopropylacrylamide) ( PNiPAM ) as a polymeric chain instead of PEG. [ 66 ]…”
Section: Mops As Porous Building Blocks For Hierarchical Self‐assemblymentioning
confidence: 99%
“…[65] The same approach was later used by Yin et al using poly(N-isopropylacrylamide) (PNiPAM) as a polymeric chain instead of PEG. [66] Hydrophobic shielding also has been used to modulate the permeability of water molecules into a MOP structure. [67] For example, Ghosh et al demonstrated that attaching hydrophobic moieties to the exposed surface of a cuboctahedral Cu-MOP enhanced its hydrolytic stability.…”
Section: Stabilitymentioning
confidence: 99%